Effect of post weld artificial aging and water cooling on microstructure and mechanical properties of friction stir welded 2198-T8 Al-Li joints. (1st October 2022) - Tao, Y.; Zhang, Z.; Xue, P.; Ni, D.R.; Xiao, B.L.; Ma, Z.Y.
Highlights: Effect of water cooling and artificial aging on FSW 2198-T8 joints was elucidated. Effect of aging on precipitate distribution features across joint was elucidated. Hardness recoveries varied in different zones of FSW joint after aging. Joint strength was effectively enhanced after aging but water cooling did not work. Abstract: Friction stir welding (FSW) under both air cooling and water cooling conditions with welding parameters of 800–1200 rpm rotation rates and 50–200 mm/min welding speeds was carried out on 2198-T8 Al-Li alloys, and post weld artificial aging was performed on the air cooled joints. No welding defects other than lazy S were observed in the nugget zone (NZ) for all joints. Under air cooling condition, the lowest hardness zone (LHZ) occurred in the heat affected zone (HAZ). FSW resulted in gradual dissolution of original T1, θ′ and δ′/β′ from the base material (BM) to the thermo-mechanically affected zone (TMAZ), and complete dissolution of all precipitates in the NZ with δ′/β′ and Guinier-Preston zones precipitating during cooling. The air cooled joints exhibited no noticeable changes in intrinsic tensile strength with a joint strength reaching 81.3% of the BM, but varied elongation with welding parameters, which was closely related to failure in the NZ and fracture along lazy S. Post weld artificial aging led to the largest hardness recovery in the TMAZ but smaller hardness recovery in the initial LHZ and the NZ. Different aging kinetics across the joint was determined by volume fraction of both original precipitate dissolution during welding and coarse particles formed during aging, and by dislocation density inherited from welding. Post weld artificial aging greatly enhanced the joint strength with the ultimate tensile strength reaching 87.3% of the BM. As compared to air cooling condition, water cooling hardly affected the NZ hardness and did not improve the joint strength, and the reason was discussed in light of precipitates, hardness changes and fracture behavior.